Access to Communication for Deaf, Hard-of-Hearing and ESL Students in Blended Learning Courses - Long, Gary L.; Vignare, Karen; Rappold, Raychel P.; Mallory, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
In an effort to better understand student perceptions of communication in blended (online and traditional) learning courses, a 22 item questionnaire was developed and sent to all students registered for these courses at a large technology-focused college during three quarters of instruction. The respondents were divided into four groups: 1) hearing, 2) deaf, 3) hard-of-hearing (D/HH), and 3) English as a second language (ESL). Their perceptions of communication and the blended learning experience were examined. While the hearing and ESL students were positive about blended learning, the findings indicated that deaf and hard-of-hearing students reported that both the quality and quantity of their interactions with the professor and other students was greatly improved by the inclusion of an online component. ESL and hearing students were also positive about the blended experience; but the greatest benefit to communication access was observed by students with a hearing loss.